Exploring factors influencing low back pain in people with non-dysvascular lower limb amputation: a national survey - Devan, Hemakumar; Hendrick, Paul; Hale, Leigh; Carman, Allan; Dillon, Michael; Riberio, Dan (Elsevier, 2017)
Background: Chronic low back pain (LBP) is a common musculoskeletal impairment in people with lower limb amputation. Given the multifactorial nature of LBP, exploring the factors influencing the presence and intensity of LBP is warranted. Objective: To investigate which physical, personal, and amputee-specific factors predicted presence and intensity of low back pain (LBP) in persons with non-dysvascular transfemoral (TFA) and transtibial amputation (TTA). Design: A retrospective cross-sectional survey. Setting: A national random sample of people with non-dysvascular TFA and TTA. Participants: Participants (N = 526) with unilateral TFA and TTA due to non-dysvascular aetiology (i.e. trauma, tumours, and congenital causes) and a minimum prosthesis usage of one year since amputation were invited to participate in the survey. The data from 208 participants (43.4% response rate) were used for multivariate regression analysis Methods (Independent variables): Personal (i.e. age, body mass, gender, work status, and presence of comorbid conditions), amputee-specific (i.e. level of amputation, years of prosthesis use, presence of phantom limb pain, residual limb problems, and non-amputated limb pain), and physical factors (i.e. pain provoking postures including standing, bending, lifting, walking,sitting, sit-to stand, and climbing stairs). Main outcome measures (Dependent variables): LBP presence and intensity. Results: A multivariate logistic regression model showed that the presence of two or more comorbid conditions (prevalence odds ratio (POR) = 4.34, p = .01), residual limb problems (POR 22 = 3.76, p<.01), and phantom limb pain (POR = 2.46, p = .01) influenced the presence of LBP. Given the high LBP prevalence (63%) in the study, there is a tendency for overestimation of PORand the results must be interpreted with caution. In those with LBP, the presence of residual limb problems (beta = 0.21, p = .01), and experiencing LBP symptoms during sit-to-stand task (beta = 0.22, p = .03) were positively associated with LBP intensity, while being employed demonstrated a negative association (beta = - 0.18, p = .03) in the multivariate linear regression model.